Tri-band Minkowski Island Patch Antenna with Complementary Split Ring Resonator at the Ground Plane - Ahmad, Badrul Hisham; Hassan, Nornikman; Abdul Aziz, M.Z.A.; Othman, A. R. (13th Conference on Microwave Techniques COMITE 2013, April 17-18, Pardubice, Czech Republic, 2013)
Abstract—The Minkoski Island patch antenna with complementary split ring resonator at the ground plane are proposed in this work. At the first stage, the normal square patch antennas mainly designed. Then, the Minkowski patch antenna was designed using 1st iteration technique and 2nd iteration technique. The Minkowski fractal shape slot was embedded in the center of the patch to form a Minkowski Island patch antenna. The next step is to apply the partial ground technique and embed the split ring resonator at the ground plane. This antenna was operating in tri-band frequency that is at 2.400 GHz, 3.500 GHz and 5.200 GHz with a return loss of - 11.868 dB, - 13.554 dB and – 18.112 dB respectively. The gain measured of this antenna is 1.286 dB, 1.410 dB and 3.945 dB. Keywords—Minkowski Island, split ring resonator, patch antenna, return loss, gain